2010
DOI: 10.1364/oe.18.007521
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of near-infrared water-leaving reflectance for satellite ocean color data processing

Abstract: The atmospheric correction algorithm employed by the NASA Ocean Biology Processing Group requires an assumption of negligible water-leaving reflectance in the near-infrared region of the spectrum. For waters where this assumption is not valid, an optical model is used to estimate near-infrared water-leaving reflectance. We describe this optical model as implemented for the sixth reprocessing of the SeaWiFS mission-long time-series (September 2009). Application of the optical model resulted in significant reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
239
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 353 publications
(243 citation statements)
references
References 13 publications
1
239
0
3
Order By: Relevance
“…Remote measurements collected at large viewing angles (large atmospheric path lengths) or through elevated aerosol loads, where the water-leaving signal is a much smaller portion of the total observed radiance at the sensor, have higher R rs λ uncertainties than those collected through shorter atmospheric paths or clear atmospheres dominated by simple Rayleigh scattering. Turbid or highly reflective waters require additional corrections to separate the atmospheric signal from the water signal, which adds additional assumptions and inherent uncertainties [53]. Similarly, R rs λ retrievals obtained in the vicinity of land, clouds, or sun glint may be contaminated by stray light or atmospheric adjacency effects.…”
Section: Fig 2 Comparison Of Giop-dc and Ground Truth (In Situ)mentioning
confidence: 99%
“…Remote measurements collected at large viewing angles (large atmospheric path lengths) or through elevated aerosol loads, where the water-leaving signal is a much smaller portion of the total observed radiance at the sensor, have higher R rs λ uncertainties than those collected through shorter atmospheric paths or clear atmospheres dominated by simple Rayleigh scattering. Turbid or highly reflective waters require additional corrections to separate the atmospheric signal from the water signal, which adds additional assumptions and inherent uncertainties [53]. Similarly, R rs λ retrievals obtained in the vicinity of land, clouds, or sun glint may be contaminated by stray light or atmospheric adjacency effects.…”
Section: Fig 2 Comparison Of Giop-dc and Ground Truth (In Situ)mentioning
confidence: 99%
“…Approximately 7300 high-quality MODIS Aqua scenes remained after quality assurance screened out scenes with 80% or more cloud and/or sunglint contaminated pixels. These remaining scenes were processed from Level-1A to Level-2 using L2GEN and its standard atmospheric correction scheme [Ahmad et al, 2010;Bailey et al, 2010], an approach which has been identified as robust for optically complex waters such as those of Chesapeake Bay, USA . We acknowledge that the standard L2GEN atmospheric correction has not formally been tested over optically shallow waters.…”
Section: Modis Aqua Processing and Analysismentioning
confidence: 99%
“…10 also has a specific implication for atmospheric correction for satellite ocean-color remote sensing. Iterative approaches with ocean reflectance in the red and NIR bands for estimating the NIR ocean contribution have long been used (Stumpf et al 2003;Bailey et al 2010;Wang et al 2013a). However, results in Fig.…”
Section: Some Satellite Ocean-color Remote-sensing Implicationsmentioning
confidence: 99%
“…, 0.05. In addition, the optical feature of insensitive ocean reflectance in red band r wN (645) implies that the current National Aeronautics and Space Administration standard satellite ocean-color atmospheric correction algorithm, which uses red ocean reflectance to estimate the NIR ocean reflectance (Bailey et al 2010), may not be applicable for highly turbid waters. The SWIR atmospheric correction algorithm is required to derive accurate satellite water property products in ocean regions such as the Subei Shoal, Yangtze River Estuary, La Plata River Estuary, and Hangzhou Bay.…”
Section: Some Satellite Ocean-color Remote-sensing Implicationsmentioning
confidence: 99%
See 1 more Smart Citation